2012
DOI: 10.1007/s11606-012-2086-5
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Improve Decision Making and Reduce Racial and Ethnic Disparities in the Management of Prostate Cancer: A Systematic Review

Abstract: OBJECTIVES: Ethnic minorities are disproportionately impacted by prostate cancer (PCa) and are at risk for not receiving informed decision making (IDM). We conducted a systematic literature review on interventions to improve: (1) IDM about PCa in screeningeligible minority men, and (2) quality of life (QOL) in minority PCa survivors. DATA SOURCES: MeSH headings for PCa, ethnic minorities, and interventions were searched in MED-LINE, Cochrane Database of Systematic Reviews, Cochrane Central Register of Controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 46 publications
(60 reference statements)
1
26
0
Order By: Relevance
“…[2][3][4][5][6] While many valuable ideas to address racial and ethnic health disparities are being pursued outside of the healthcare system, Finding Answers focuses specifically on what can be accomplished once regular access to healthcare services is achieved. Thus, the reviews focused on interventions that occur in or have a sustained linkage to a healthcare delivery setting; programs that were strictly communitybased were outside the scope of the project.…”
Section: Findings From the Systematic Reviewsmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4][5][6] While many valuable ideas to address racial and ethnic health disparities are being pursued outside of the healthcare system, Finding Answers focuses specifically on what can be accomplished once regular access to healthcare services is achieved. Thus, the reviews focused on interventions that occur in or have a sustained linkage to a healthcare delivery setting; programs that were strictly communitybased were outside the scope of the project.…”
Section: Findings From the Systematic Reviewsmentioning
confidence: 99%
“…The prostate cancer review focused on the importance of informed decision making for addressing prostate cancer among racial and ethnic minority men. 6 Educational programs were the most effective intervention for improving knowledge among screening-eligible minority men. Cognitive behavioral strategies improved quality of life for minority men treated for localized prostate cancer.…”
Section: Findings From the Systematic Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 While evidence for and against PCS is inconsistent, current guidelines fail to address racial and ethnic disparities associated with PCa, and hence, potentially adverse consequences of discontinuing testing for high-risk groups such as AA males. 11 The research used to develop the current guidelines lacked sufficient numbers of AA and other racial/ethnic minorities. 12,13 The purpose of the study is as indicated in the next paragraph.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggest they might be helpful with minority populations. 3,4 This intervention was a video decision tool, but one could easily see motivated health systems hosting these videos on their webpages, on their Facebook accounts and even pushing them to patients. As the current, computer savvy generation ages, one can imagine innumerable opportunities for asynchronous communication and education.…”
mentioning
confidence: 99%